Chronic Lithium-Induced Cardiotoxicity: A Case Report and Lessons for Clinical Practice - Amir Heidari; Nafise Mohamadizade; Arman Hasanzade; Morteza Fazlekhoda (Case Reports in Medicine, 2025)
Discussion: Lithium has a narrow therapeutic range, which can lead to toxicity in the absence of routine monitoring. Lithium toxicity can cause serious cardiac effects and rhythm disturbances that are often overlooked because these manifestations are rare. Cardiac manifestations include arrhythmias, bradycardia, collapse, hypotension, myocardial infarction, and even death. Additionally, lithium toxicity can present with various electrocardiographic abnormalities such as T-wave inversion, sinoatrial block, PR interval prolongation, QT prolongation/dispersion, and ventricular tachyarrhythmias. Clinicians should be aware of the potential cardiac effects of lithium toxicity and consider it in patients undergoing lithium treatment. A thorough understanding of these manifestations is essential, as the wide range of symptoms can be misleading without adequate knowledge.